ANALISIS PEMETAAN BUDAYA ORGANISASI MENNGGUNAKAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) PADA FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS DIPONEGORO - Yona Kusumaningtyas; Ismi Darmastuti (Faculty of Economics and Business Diponegoro University, 2016)
Organization Culture is need to be developed and adapted with the developments andchanges of the organization. Nowadays, many companies do not understand theimportance of organization culture as a fundamental factor in the company. Faculty ofEconomics and Business Universitas Diponegoro have the vision, mission, values, andgoals to be achieved. With the mapping of cultural profile of current and futureexpectations may be one input for an institution to prepare for the change and understandwhether the vision, mission, and values that have been defined it is understood andpreserved as the organization's culture.This research was conducted by survey method using OCAI (Organizational CultureAssessment Instrument). The survey conducted on alumni, students, staff, and faculty witha sample size of each stratum 25 people. So great the entire sample was 100 people. Thisresearch uses descriptive quantitative approach so as to reveal and analyze the culturalprofile FEB Undip current and expected in the next few years.The results obtained from this study showed a difference between the perception of thecurrent culture of alumni, students, staff, and faculty. Alumni, staff, and faculty feel thatthe dominant culture of the company is the culture clan. Meanwhile, students feel thecurrent dominant culture is a culture of hierarchy. There are cultural similaritiesexpected by all stakeholders ie culture clan. There seems to be a trend toward morepowerful clan culture as a type of culture is expected. This cultural profile picture FEBUndip can be used for decision making in accordance with the vision, mission andobjectives of the FEB Undip.Keywords: Mapping Cultural Organization, OCAI, FEB Undip, Quantitative Descriptive